Deep Dark Futures: Foresighting Human Impacts on Mesopelagic Ecosystem Services - Ben Scoulding; Alistair J. Hobday; Rowan Trebilco; Heidi Pethybridge; Ingrid van Putten; Katherine Baker; Karen Evans; David Green; Eriko Hoshino; Haris Kunnath; Clothilde Langlais; Tim P. Lynch; et al. (Fish and Fisheries, 2026)
Most of the global mesopelagic zone lies beyond the jurisdiction of any single government or entity, making equitable access and sustainable management for ecosystem services (ES) difficult. Here, a foresighting approach was used to examine the plausible consequences of four speculative scenarios of human activity on the mesopelagic zone and its associated ES. Large‐scale Harvest represented the provisioning ES, with concerns over unsustainable removal of mesopelagic biota. Climate Mitigation, a regulating ES, involved harvesting and then dumping mesopelagic biota to maximise carbon drawdown. In Geopolitical Manoeuvring, the scenario focused on cultural ES; mesopelagic fisheries were used as a geopolitical instrument to assert claims over ocean spaces. Finally, Mineral Extraction, a supporting ES, considered the impact of deep‐sea mining on mesopelagic ecosystems. Drivers and indicators for each scenario were identified, and qualitative network models were created to assess impact on the different system components using press perturbations. Model outputs highlighted the central role that mesopelagic biota play in supporting and regulating other ecosystem components and the likely negative impacts of reduced biomass on higher order predators and ocean carbon storage. Interestingly, biological indicators performed poorly as early warning signals of change across all scenarios; instead, the most effective indicators were related to science and technology, economics and governance. International agreements for sustainable use of the mesopelagic zone are needed to avoid loss of ES underpinning all scenarios. While this foresighting focused on the mesopelagic zone, the approach of developing scenarios, models and indicators has broader applicability to studies of other systems.

Microclimate vulnerability under coupled effects of changing climate and forest structure - Joanna Lumbsden-Pinto; Tim Green; Kathy Schwager; Martin Dovciak (Agricultural and Forest Meteorology, 2025)

Combining Observations and Models: A Review of the CARDAMOM Framework for Data‐Constrained Terrestrial Ecosystem Modeling - Matthew A. Worden; T. Eren Bilir; A. Anthony Bloom; Jianing Fang; Lily P. Klinek; Alexandra G. Konings; Paul A. Levine; David T. Milodowski; Gregory R. Quetin; T. Luke Smallman; Yinon M. Bar‐On; Renato K. Braghiere; et al. (Global Change Biology, 2025)
The rapid increase in the volume and variety of terrestrial biosphere observations (i.e., remote sensing data and in situ measurements) offers a unique opportunity to derive ecological insights, refine process‐based models, and improve forecasting for decision support. However, despite their potential, ecological observations have primarily been used to benchmark process‐based models, as many past and current models lack the capability to directly integrate observations and their associated uncertainties for parameterization. In contrast, data assimilation frameworks such as the CARbon DAta MOdel fraMework (CARDAMOM) and its suite of process‐based models, known as the Data Assimilation Linked Ecosystem Carbon Model (DALEC), are specifically designed for model‐data fusion. This review, motivated by a recent CARDAMOM community workshop, examines the development and applications of CARDAMOM, with an emphasis on its role in advancing ecosystem process understanding. CARDAMOM employs a Bayesian approach, using a Markov Chain Monte Carlo algorithm to enable data‐driven calibration of DALEC parameters and initial states (i.e., carbon pool sizes) through observation operators. CARDAMOM's unique ability to retrieve localized model process parameters from diverse datasets—ranging from in situ measurements to global satellite observations—makes it a highly flexible tool for analyzing spatially variable ecosystem responses to environmental change. However, assimilating these data also presents challenges, including data quality issues that propagate into model skill, as well as trade‐offs between model complexity, parameter equifinality, and predictive performance. We discuss potential solutions to these challenges, such as reducing parameter equifinality by incorporating new observations. This review also offers community recommendations for incorporating emerging datasets, integrating machine learning techniques, strengthening collaboration with remote sensing, field, and modeling communities, and expanding CARDAMOM's relevance for localized ecosystem monitoring and decision‐making. CARDAMOM enables a deep, mechanistic understanding of terrestrial ecosystem dynamics that cannot be achieved through empirical analyses of observational datasets or weakly constrained models alone.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Cerebrovascular function and its association with systemic artery function and stiffness in older adults with and without mild cognitive impairment - Tom G. Bailey; Timo Klein; Annelise L. Meneses; Kayla B. Stefanidis; Stefanie Ruediger; Daniel J. Green; Tim Stuckenschneider; Stefan Schneider; Christopher D. Askew (European Journal of Applied Physiology, 2022)
Purpose Our aim was to compare cerebrovascular and systemic vascular function between older adults with and without mild cognitive impairment (MCI), and to determine which measures of vascular function best predict the presence of MCI. Methods In 41 adults with MCI and 33 adults without MCI (control) we compared middle cerebral artery velocity (MCAv) and cerebrovascular pulsatility index (PI) at rest, cerebrovascular reactivity to CO 2 , and responsiveness to changes in blood pressure (%∆MCAv/%∆MAP). Systemic vascular function was assessed by flow-mediated dilation (FMD) and stiffness by pulse wave velocity (PWV). Results Cerebrovascular PI was higher in MCI compared with control (mean ± SD: 1.17 ± 0.27 vs. 1.04 ± 0.21), and MCI exhibited a lower %∆MCAv/%∆MAP (1.26 ± 0.44 vs. 1.50 ± 0.55%). Absolute ( p = 0.76) and relative cerebrovascular reactivity to CO 2 ( p = 0.34) was similar between MCI and control. When age was included as a covariate the significant difference in cerebral PI between groups was lost. PWV was higher (13.2 ± 2.2 vs. 11.3 ± 2.5 m s −1 ) and FMD% (4.41 ± 1.70 vs. 5.43 ± 2.15%) was lower in MCI compared with control. FMD% was positively associated with PI across the cohort. Logistic regression analysis indicated that FMD and PWV significantly discriminated between MCI and controls, independent of age, whereas the inclusion of cerebrovascular measures did not improve the predictive accuracy of the model. Conclusion These findings raise the possibility that early changes in systemic vascular stiffness and endothelial function may contribute to altered cerebrovascular haemodynamics and impaired cognitive function, and present potential targets for prevention and treatment strategies in people with MCI.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Characterizing Canopy Openness in Open Forests: Spherical Densiometer and Canopy Photography Are Equivalent but Less Sensitive than Direct Measurements of Solar Radiation - Emily Russavage; Jake Thiele; Joanna Lumbsden-Pinto; Kathy Schwager; Tim Green; Martin Dovciak (Journal of Forestry, 2021)
In forest ecosystems, canopy openness affects understory light availability, plant growth, and tree species recruitment, thus shaping future forest composition, structure, and functional diversity. Foresters must correctly and quickly measure canopy openness to meet their management objectives. To help guide the selection of an appropriate method for measuring canopy openness, we compared three common techniques that vary in cost, complexity, and time required for measurements and data processing: smartphone-based hemispherical photography, spherical densiometer measurements, and direct measurements of solar radiation (using AccuPAR ceptometer). We measured canopy openness using these three methods on 28 permanent forest health monitoring plots in pine-oak forests of the Central Pine Barrens of Long Island in New York State. By analysis of variance and regression analyses, we found the three methods (particularly densiometer and hemispherical photographs) yielded broadly equivalent and strongly positively correlated descriptions of canopy openness. The direct measurements of solar radiation seemed to have a greater potential to detect subtle variation in forest understory light. Forest managers may sufficiently characterize canopy openness using quick and cheap methods (e.g., spherical densiometers) and avoid larger costs of devices for direct light measurements (e.g., ceptometers) and the larger data-processing times of hemispherical photography.

Ten‐year assessment of the 100 priority questions for global biodiversity conservation - Tommaso Jucker; Bonnie Wintle; Gorm Shackelford; Pierre Bocquillon; Jan Laurens Geffert; Tim Kasoar; Eszter Kovacs; Hannah S. Mumby; Chloé Orland; Judith Schleicher; Eleanor R. Tew; Aiora Zabala; et al. (Conservation Biology, 2018)
In 2008, a group of conservation scientists compiled a list of 100 priority questions for the conservation of the world's biodiversity. However, now almost a decade later, no one has yet published a study gauging how much progress has been made in addressing these 100 high‐priority questions in the peer‐reviewed literature. We took a first step toward reexamining the 100 questions to identify key knowledge gaps that remain. Through a combination of a questionnaire and a literature review, we evaluated each question on the basis of 2 criteria: relevance and effort. We defined highly relevant questions as those that – if answered – would have the greatest impact on global biodiversity conservation and quantified effort based on the number of review publications addressing a particular question, which we used as a proxy for research effort. Using this approach, we identified a set of questions that, despite being perceived as highly relevant, have been the focus of relatively few review publications over the past 10 years. These questions covered a broad range of topics but predominantly tackled 3 major themes: conservation and management of freshwater ecosystems, role of societal structures in shaping interactions between people and the environment, and impacts of conservation interventions. We believe these questions represent important knowledge gaps that have received insufficient attention and may need to be prioritized in future research.

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

‘ Candidatus Adiutrix intracellularis’, an endosymbiont of termite gut flagellates, is the first representative of a deep‐branching clade of Deltaproteobacteria and a putative homoacetogen - Wakako Ikeda‐Ohtsubo; Jürgen F. H. Strassert; Tim Köhler; Aram Mikaelyan; Ivan Gregor; Alice C. McHardy; Susannah Green Tringe; Phil Hugenholtz; Renate Radek; Andreas Brune (Environmental Microbiology, 2016)
Summary Termite gut flagellates are typically colonized by specific bacterial symbionts. Here we describe the phylogeny, ultrastructure and subcellular location of ‘ Candidatus Adiutrix intracellularis’, an intracellular symbiont of Trichonympha collaris in the termite Zootermopsis nevadensis . It represents a novel, deep‐branching clade of uncultured Deltaproteobacteria widely distributed in intestinal tracts of termites and cockroaches. Fluorescence in situ hybridization and transmission electron microscopy localized the endosymbiont near hydrogenosomes in the posterior part and near the ectosymbiont ‘ Candidatus Desulfovibrio trichonymphae’ in the anterior part of the host cell. The draft genome of ‘ Ca . Adiutrix intracellularis’ obtained from a metagenomic library revealed the presence of a complete gene set encoding the Wood–Ljungdahl pathway, including two homologs of fdhF encoding hydrogenase‐linked formate dehydrogenases (FDH H ) and all other components of the recently described hydrogen‐dependent carbon dioxide reductase (HDCR) complex, which substantiates previous claims that the symbiont is capable of reductive acetogenesis from CO 2 and H 2 . The close phylogenetic relationship between the HDCR components and their homologs in homoacetogenic Firmicutes and Spirochaetes suggests that the deltaproteobacterium acquired the capacity for homoacetogenesis via lateral gene transfer. The presence of genes for nitrogen fixation and the biosynthesis of amino acids and cofactors indicate the nutritional nature of the symbiosis.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Time-course of vascular adaptations during 8 weeks of exercise training in subjects with type 2 diabetes and middle-aged controls - Tim H. A. Schreuder; Daniel J. Green; Jean Nyakayiru; Maria T. E. Hopman; Dick H. J. Thijssen (European Journal of Applied Physiology, 2015)

Acute anxiety increases the magnitude of the cold shock response before and after habituation - Martin James Barwood; Jo Corbett; Richard Green; Tim Smith; Perry Tomlin; Lydia Weir-Blankenstein; Michael J. Tipton (European Journal of Applied Physiology, 2013)

Beta-papillomavirus DNA loads in hair follicles of immunocompetent people and organ transplant recipients - Sönke Weissenborn; Rachel E. Neale; Tim Waterboer; Damiano Abeni; Jan Nico Bouwes Bavinck; Adele C. Green; Catherine A. Harwood; Sylvie Euvrard; Mariet C. W. Feltkamp; Maurits N. C. de Koning; Luigi Naldi; Wim G. V. Quint; et al. (Medical Microbiology and Immunology, 2012)

Effects of altitude exposure on brain natriuretic peptide in humans - David Woods; Tim Hooper; Pete Hodkinson; Steve Ball; Rob Wakeford; Bob Peaston; Claire Bairsto; Nic Green; Adrian Mellor (European Journal of Applied Physiology, 2011)

Effect of Src kinase inhibition on metastasis and tumor angiogenesis in human pancreatic cancer - Ivan Ischenko; Markus Guba; Maksim Yezhelyev; Armine Papyan; Gerald Schmid; Tim Green; Michael Fennell; Karl-Walter Jauch; Christiane J. Bruns (Angiogenesis, 2007)

Src kinase promotes adhesion-independent activation of FAK and enhances cellular migration in tamoxifen-resistant breast cancer cells - Stephen Hiscox; Nicola J. Jordan; Liam Morgan; Tim P. Green; Robert I. Nicholson (Clinical & Experimental Metastasis, 2007)

Contribution of NMDA and non-NMDA receptors to synaptic transmission from the brachium of the inferior colliculus to the medial subdivision of the medial geniculate nucleus in the rabbit - Tim J. Webber; Edward J. Green; Ray W. Winters; Neil Schneiderman; P. M. McCabe (Experimental Brain Research, 1999)